2003
DOI: 10.1046/j.1600-6143.2003.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Plasma Exchange Therapy in Thrombotic Microangiopathy After Renal Transplantation

Abstract: Thrombotic microangiopathy (TMA) in renal transplant recipients is commonly associated with calcineurin inhibitors (CNIs), though several factors such as vascular rejection, viral infections and other drugs may play a contributory role. We report a series of 29 patients with TMA, all of whom were on CNIs. Though plasma exchange (PEx) is widely used to treat TMA, therapeutic guidelines are not well defined. All our patients were treated with PEx and discontinuation of CNIs. Thrombotic microangiopathy was diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 32 publications
2
80
2
2
Order By: Relevance
“…Our review of recent studies indicated that graft survival or recipient mortality differed profoundly between TMA after kidney transplantation and TMA after nonrenal "vital" organ transplantation (Table 5); TMA can be life-threatening in recipients after heart or lung transplantation. Survival of patients who had TMA and were treated with PE and/or CNI conversion after LDLT in our report was poorer than that of overall TMA (2,3) and even less than that of TMA after renal transplantation (6,7,20,27,28). That considerable difference is not surprising because the burden of comorbid disease in the liver transplantation population negatively affects survival when compared with that of patients after kidney transplantation.…”
Section: Outcomecontrasting
confidence: 58%
See 1 more Smart Citation
“…Our review of recent studies indicated that graft survival or recipient mortality differed profoundly between TMA after kidney transplantation and TMA after nonrenal "vital" organ transplantation (Table 5); TMA can be life-threatening in recipients after heart or lung transplantation. Survival of patients who had TMA and were treated with PE and/or CNI conversion after LDLT in our report was poorer than that of overall TMA (2,3) and even less than that of TMA after renal transplantation (6,7,20,27,28). That considerable difference is not surprising because the burden of comorbid disease in the liver transplantation population negatively affects survival when compared with that of patients after kidney transplantation.…”
Section: Outcomecontrasting
confidence: 58%
“…Incidence of posttransplantation TMA was reported collectively after kidney transplantation (6,7,20,27,28), suggesting that recurrent TMA among renal transplant recipients with native kidney HUS/TTP should be distinguished from posttransplantation de novo TMA among those with other native renal disorders: Incidence of the former tends to be much higher than that of the latter (Table 5). Incidence of TMA after nonrenal organ transplantation remains poorly discussed in a few papers (29 -31), but TMA in nonrenal transplant recipients seems to be more common than de novo TMA in renal transplant recipients.…”
Section: Incidencementioning
confidence: 99%
“…According to the US Renal Data System, after transplantation, only 0.8% of patients develop a de novo TMA (70). However, single center studies reported a higher incidence ranging between 4% and 14% (71,72). TMA usually develops within the first 1 year after transplantation (73).…”
Section: Thrombotic Microangiopathymentioning
confidence: 99%
“…Withdrawal or reduction of CNI or mTOR inhibitors may be followed by remission in milder cases. Plasma exchange in addition to CNI withdrawal can contribute to graft salvage (71,73,84). Recently, cases of remission with eculizumab in post-transplant de novo TMA in transplant have been reported (85)(86)(87).…”
Section: Thrombotic Microangiopathymentioning
confidence: 99%
“…1) [1,2,3,4,5,6,7]. When the lesions predominate in the renal microvasculature, and the triad of microangiopathic hemolytic anemia, thrombocytopenia and acute renal failure is present, it is known as the hemolytic-uremic syndrome (HUS) [1,2,3,6,7,8,9,10,11,12]. …”
Section: Introductionmentioning
confidence: 99%